Islamic Education in China: Rebuilding Communities and Expanding Local and International Networks - jackie armijo (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Over the last twenty years a wide range of Islamic educational opportunities have been developed to meet the needs of Chinaâ€™s 20 million plus Muslim population. In addition to mosque schools, government Islamic colleges, and independent Islamic colleges, a growing number of students have gone overseas to continue their studies at international Islamic universities in Egypt, Syria, Saudi Arabia, Pakistan, Iran, and Malaysia.Â